Stages of change and health-related quality of life among employees of an institution - Liau , Siow Yen; A syafie, Asrul; Mohamed Ibrahim, Mohamed Izham; Hassali, Mohamed Azmi; Othman, Ahmad Tajuddin; Nik Mohamed, Mohamad Haniki; A Hamdi, Menal (2011 Blackwell Publishing Ltd Health Expectations, 2011)
Background Transtheoretical Model of change has been used successfully in promoting behaviour change. Objective To examine the relationships between health-related quality of life (HRQoL) scores with the stages of change of adequate physical activity and fruit and vegetables intake. Design This was a cross-sectional study conducted among employees of the main campus and Engineering campus of Universiti Sains Malaysia (USM) during October 2009 and March 2010. Main variables studied: Data on physical activity and fruit and vegetable intake was collected using the WHO STEPS instrument for chronic disease risk factors surveillance. The Short Form-12 health survey (SF-12) was used to gather information on participants HRQoL. The current stages of change are measured using the measures developed by the Pro-Change Behaviour Systems Incorporation. Statistical analysis: One way ANOVA and its non-parametric equivalent Kruskal-Wallis were used to compare the differences between SF-12 scores with the stages of change. Results A total of 144 employees were included in this analysis. A large proportion of the participants reported inadequate fruits and vegetable intake (92.3%) and physical activity (84.6%). Mean physical and mental component scores of SF-12 were 50.39 (SD = 7.69) and 49.73 (SD = 8.64) respectively. Overall, there was no statistical significant difference in the SF-12 domains scores with regards to the stages of change for both the risk factors. Conclusions There were some evidence of positive relationship between stages of change of physical activity and fruit and vegetable intake with SF-12 scores. Further studies need to be conducted to confirm this association.